Factors Influencing Generation Z's Purchasing Intention In BSI Mobile Gold Installments - Amelia, Siska; Aisyah, Muniaty (JPS (Jurnal Perbankan Syariah), 2024)
This study aims to analyze the influence of corporate image, content marketing, and price on the interest in buying BSI Mobile gold installment products among Generation Z. This study uses a quantitative approach with sampling through a purposive sampling method that was tested on 100 respondents who are Instagram followers @lifewithbsi from generation Z. The primary data source used was an online questionnaire distribution. The analysis technique used is the structural equation model - partial least square (SEM-PLS) using the SmartPLS analysis tool. This study found that corporate image and content marketing positively influence buying interest. At the same time, price does not affect buying interest. Theoretically, this study can provide information and supporting literature for the academic community in similar studies in the future. Practically, this study can be helpful to BSI in terms of corporate image and content marketing to increase the interest of customers and prospective customers from Generation Z in using its products.